CXCL1 is upregulated during the development of ileus resulting in decreased intestinal contractile activity. Issue 3 (13th November 2019) - Docsa, Tibor; Bhattarai, Deepa; Sipos, Adam; Wade, Charles E.; Cox, Charles S.; Uray, Karen
Abstract: Background: Although the development of ileus is widespread and negatively impacts patient outcomes, the mechanism by which ileus develops remains unclear. The purpose of our study was to examine the contribution of myogenic mechanisms to postoperative ileus development and the involvement of inflammation in mediating intestinal smooth muscle dysfunction. Methods: Contractile activity and the effects of CXCL1 were studied in a gut manipulation model. Key Results: Contraction amplitude in the ileum decreased significantly, while tone increased significantly in response to gut manipulation. Differences in contraction amplitude were affected by tetrodotoxin at earlier time points, but not at later time points. Agonist‐induced contractions in the small intestine decreased significantly with ileus development. Intestinal transit slowed significantly after the induction of ileus. Myosin light chain phosphorylation was significantly decreased and edema increased significantly in the intestinal wall. Conditioned media from mechanically activated macrophages depressed intestinal contractile activity. CXCL1 (GroA) was significantly increased in the mechanically activated macrophages and intestinal smooth muscle within 1 hour after induction of ileus compared with control cells and sham animals, respectively. Treatment with CXCL1 significantly decreased contraction amplitude and agonist‐induced contractile activity and increased tone in the small intestine. In the gut manipulation model, treatment with a CXCR2 antagonist prevented the decrease in agonist‐induced contractile activity but not contraction amplitude. Conclusions & Inferences: These data suggest that CXCL1, released from macrophages during intestinal wall stress, can suppress intestinal contractile activity. CXCL1 is a potential target for preventing or treating ileus in trauma patients. Abstract : Mechanism for decreased intestinal smooth muscle function in ileus.